Sacituzumab govitecan and radiotherapy in metastatic, triple-negative, and BRCA-mutant breast cancer patient with active brain metastases: A case report - di Mauro, Pierluigi; Schivardi, Greta; Pedersini, Rebecca; Laini, Lara; Esposito, Andrea; Amoroso, Vito; Laganà, Marta; Grisanti, Salvatore; Cosentini, Deborah; Berruti, Alfredo (Frontiers in Oncology, 2023)
Background: Triple-negative breast cancer (TNBC) is an aggressive cancer subtype, owing to its high metastatic potential: patients who develop brain metastases (BMs) have a poor prognosis due to the lack of effective systemic treatments. Surgery and radiation therapy are valid options, while pharmacotherapy still relies on systemic chemotherapy, which has limited efficacy. Among the new treatment strategies available, the antibody-drug conjugate (ADC) sacituzumab govitecan has shown an encouraging activity in metastatic TNBC, even in the presence of BMs. Case presentation: A 59-years-old woman was diagnosed with early TNBC and underwent surgery and subsequent adjuvant chemotherapy. A germline pathogenic variant in BRCA2 was revealed after genetic testing. After eleven months from completion of adjuvant treatment, she had pulmonary and hilar nodal relapse and began first-line chemotherapy with carboplatin and paclitaxel. However, after only three months from starting treatment, she experienced relevant disease progression, due to the appearance of numerous and symptomatic BMs. Sacituzumab govitecan 10 mg/kg was started as second-line treatment as part of the Expanded Access Program. She reported symptomatic relief after the first cycle and received whole-brain radiotherapy (WBRT) concomitantly to sacituzumab govitecan treatment. The subsequent CT scan showed an extracranial partial response and a near-to-complete intracranial response; no grade 3 adverse events were reported, even if sacituzumab govitecan was reduced to 7.5 mg/kg due to persistent G2 asthenia. After 10 months from starting sacituzumab govitecan, a systemic disease progression was documented, while intracranial response was maintained. Conclusions: This case report supports the potential efficacy and safety of sacituzumab govitecan in the treatment of early-recurrent and BRCA-mutant TNBC. Despite the presence of active BMs, our patient had a progression-free survival (PFS) of 10 months in the second-line setting and sacituzumab govitecan was safe when administered together with radiation therapy. Further real-world data are warranted to confirm sacituzumab govitecan efficacy in this patients’ population.